Methodological Principles of Assessing the Volume of Investment Influx from Non-State Pension Funds into the Economy of Ukraine - Dmitro Leonov (International Economic Policy, 2004)
This article addresses the processes of forming investment resources from nonstate pension funds under current conditions in Ukraine and the laws and regula tions that define the principles of the formation of in vestment institutions. Based on factors that in the near est future will affect the decisionmaking process by which different kinds of investors make payments to non state pension funds, we develop a procedure for assessing the volume of investment influx from nonstate pension funds into the economy and propose a procedure for long and shortterm prognosis of the volume of investment in flux from nonstate pension funds into the Ukrainian economy.